Development of a checklist of quality indicators for clinical trials in resource-limited countries: The French National Agency for Research on AIDS and Viral Hepatitis (ANRS) experience. (April 2013) - Hanna, Mina; Minga, Albert; Fao, Paulin; Borand, Laurence; Diouf, Assane; Mben, Jean-Marc; Gad, Rita R; Anglaret, Xavier; Bazin, Brigitte; Chene, Geneviève; ,
Background: Since 1994, the French National Agency for Research on AIDS and Viral Hepatitis (ANRS) has funded research sites in resource-limited countries (RLCs). These sites implement research on human immunodeficiency virus (HIV) infection and Hepatitis C. In parallel, international regulations and recommendations for clinical trials have evolved and proliferated. However, little guidance exists on how these should be interpreted and applied within academic trials and in the context of RLCs. After developing a specific Ethical Charter for research in developing countries in 2002, ANRS developed a set of quality indicators (QIs) as a monitoring tool for assessing compliance to international guidelines. Purpose: We describe here the development process, QIs adopted, and areas for improvement. Methods: In 2008, a group of experts was convened that included a researcher representing each ANRS site (Cote d'Ivoire, Senegal, Cameroun, Burkina Faso, Egypt, and Cambodia). Our structuring interaction development process combined evidence and expert opinion in two nominal group meetings to identify (1) clinical trial processes involved, (2) issues specific to RLCs in terms of Good Clinical Practice (GCP) and the application of ethical recommendations, and (3) checklists of QIs adapted to clinical trials conducted in RLCs. Results: The trial process reviewed and proposed for RLCs was mostly similar to the one produced in wealthier countries. The scheme generated by our work group added two further processes: 'drug management' and 'biological investigations'. Specific issues regarding trial management in RLCs were therefore described for eight trial steps (1) protocol conception and seeking authorizations, (2) participant enrollment and follow-up, (3) site monitoring, (4) drug management, (5) biological investigations, (6) record management, (7) data management, and (8) site closeout. A total of 58 indicators were identified with at least one indicator for each trial process. Limitations: Some trial activities require further consideration, that is, in the case of vulnerable participants (children, pregnant women). Proposed indicators are the result of expert consensus and reflect their experience in the HIV field. Relevance to existing trials and extrapolation to other fields must be assessed. Conclusions: This innovative program allowed ANRS sites located in RLCs to share their GCP implementation experiences in order to build a list of relevant indicators for clinical trials. The next step is to collect data from ongoing HIV and hepatitis C trials in these settings and will assess the relevance of these indicators to document current quality of performance among trials in resource-limited settings.